Pengembangan Aplikasi Web Portofolio Kegiatan Pengabdian Masyarakat pada Perguruan Tinggi Menggunakan Metode Extreme Programming - Lukman Rosyidi; Maulana Fakih Latief; Siti Aisah; Hany Hidianti; Noviana Nur Shanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The documentation process for community service activities is often not centralized and not well-published, resulting in activity information not being systematically organized and difficult to access by both internal parties and the wider community. This study developed a web-based community service activity portfolio application with a case study at Nurul Fikri College of Technology. The system development process applied the Extreme Programming (XP) method, consisting of planning, design, coding, and testing stages. The application was built using the Laravel framework with a Model-View-Controller (MVC) approach and supported by MySQL as the database management system. The results of the study indicate that the community service activity portfolio web application was successfully developed and is able to assist the documentation, management, and publication of activities in a more structured manner. The application provides various features, such as managing activity portfolios, services, partners, expertise, submissions, activity documentation, and managing other supporting data. Based on the results of testing using the Black Box User Acceptance Testing (UAT) method, all features in the system successfully implemented according to their expected functions and user requirements.